Nurse Documentation of Child Weight-Related Health Promotion at Age Four in Sweden - Anna Svensson Sehic; Mikaela Persson; Eva K. Clausson; Eva-Lena Einberg (MDPI AG, 2021)
(1) Background: Overweight and obesity in children have increased worldwide and tend to persist into adolescence and adulthood. The Child Health Service (CHS) has an important role in providing health-promotive interventions, and such interventions are required to be documented in a child's health record. The aim of the study was to investigate Child Health Care (CHC) nurses' documentation of weight-related, health-promotive interventions in the Child Health Care Record (CHCR) regarding lifestyle habits in connection to the four-year visit. (2) Methods: A record review of 485 CHCRs using a review template was accomplished. Of the included CHS units, four used electronic records and two used paper records. Chi-square tests and Spearman's rank-order correlations were used to analyse data. (3) Results: The results showed that CHC nurses document interventions regarding lifestyle habits to a low extent, although children with overweight/obesity seemed to undergo more interventions. There was also a difference between electronic and paper records. (4) Conclusions: The consequences of not documenting the interventions in the CHCR make it difficult to follow up and demonstrate the quality of the CHC nurse's work. There is a need for more research to gain a deeper understanding of the reasons that the work of CHC nurses is not visible in children's health records.